The Improvement of Science Learning Outcomes and Intrapersonal Intelligence Through Course Review Horay of Third Grade Students at MI Mazra’atul Ulum 01 Lamongan - Ikrima, Ikrima (Indonesian Journal of Science Learning (IJSL), 2021)
This research was conducted because the learning process is lack student’s enthusiasm and passion, it tends to be not interested learning. The previous student learning outcomes were only 13% who reach the minimum completeness criteria. Learning so far has used the lecture method so it is necessary to apply a course review horay strategy. This research was conducted at MI Mazra’atul Ulum 01 Lamongan. The method used in this research is classroom action research which consists of 2 cycles, each cycle through 4 stages, namely planning, implementation, observation, and reflection. Data were obtained through interviews, questionnaires, worksheets and documentation. Data on student learning outcomes were analyzed by SPSS to determine the increase in students learning outcomes and intrapersonal intelligence in each cycle. The results showed that: (1) The implementation of the course review horay strategy has done well because it is able to increase the activities of teachers and students. In the pre-cycle teacher, activity has a percentage of 58% (less), cycle 1 has a percentage of 71% (good), and cycle 2 has a percentage of 73% (good). In the pre-cycle student’s activity has a percentage of 42% (less), cycle 1 has a percentage of 58% (less), and cycle 2 has a percentage of 83% (good). (2) Data on student learning outcomes in the pre-cycle has a percentage of 13% with an average of 48.8 (less), in cycle 1 got a percentage of 94% with an average of 78.2 (good) and in cycle 2 got a percentage of 94% with an average 78.6 (good). (3) Intrapersonal intelligence in pre-cycle has a percentage of 40%, cycle 1 has a percentage of 88%, and cycle 2 has a percentage of 96%.